Patterns of acquisition and consumption of milk and other dairy products in Bamako, Mali - Sissoko, K.; Debrah, S.K.; Soumare, S. (International Livestock Centre for Africa, 1992)
This study describes the patterns and levels of consumption of locally produced, factory-manufactured and directly imported, and readily usable dairy products in the city of Bamako, Mali. It covers a sample of 240 urban households stratified by wealth category (rich, medium income and poor). Taking all dairy products together, an average consumption of 18 kg liquid milk equivalent (LME) person per year was estimated. Rich households consumed an average of 22 kg LME/person per year and spent 1.8 percent of their monthly income on dairy products. Poor housholds consumed an average of 6.4 kg LME/person per year and spent 3.4 percent of their monthly income on dairy products. Locally produced fresh milk, factory reconstituted milk and directly imported readily usable milk were among the most frequently consumed dairy products. Financial difficulty was cited as the most important reason for the low level and irregularity of consumption of dairy products by the poor households. Consumers considered convenience in terms of proximity, favorable terms of purchase and product quality when acquiring dairy products. In general, between 71 percent and 86 percent of total expenditure on dairy products was on directly imported products. Only between 9 and 20 percent was spent on domestically produced dairy products.